Protocol of a randomised controlled phase II clinical trial investigating PREoperative endoscopic injection of BOTulinum toxin into the sphincter of Oddi to reduce bile leakage after hepatic resection: the PREBOT-II trial - Mack, Claudia; Klaiber, Ulla; Sauer, Peter; Benner, Laura; Baumann, Lukas; Martin, Eike; Mehrabi, Arianeb; Büchler, Markus W.; Hackert, Thilo (BMJ open, 2023)
Introduction Bile leakage represents a major cause of morbidity following hepatic resection. Although most patients can be managed non-operatively, this complication requires diagnostics and therapeutic interventions. Preoperative endoscopic injection of botulinum toxin (BTX) into the sphincter of Oddi represents an innovative approach to prevent bile leakage. The aim of the PREBOT-II trial is to generate the first randomised controlled trial data on the safety, feasibility and efficacy of preoperative endoscopic BTX injection into the sphincter of Oddi to prevent bile leakage following hepatic resection. - Methods and analysis The PREBOT-II trial is an investigator-initiated, exploratory, multicentre, randomised, controlled, open-label, phase II clinical trial with two parallel study groups. 70 patients scheduled for hepatic resection will be randomised to either the intervention or the control group. Patients of the intervention group will undergo preoperative endoscopic injection of BTX into the sphincter of Oddi 3-10 days before surgery, whereas in the control group only hepatic resection will be performed. The primary endpoint is the occurrence of a postoperative bile leakage within 30 days after hepatic resection according to the definition of the International Study Group of Liver Surgery. The secondary endpoints comprise further postoperative morbidity parameters such as severity of postoperative bile leakage, post-hepatectomy haemorrhage or liver failure, mortality and quality of life up to 3 months after hepatic resection. Safety and feasibility of the procedure will also be recorded. - Ethics, funding and dissemination The PREBOT-II trial has been approved by the German Federal Institute for Drugs and Medical Devices (reference number 4044932) and the Ethics Committee of Heidelberg University (reference number AFmu-558/2021). This trial is supported by the German Federal Ministry of Education and Research. The results will be presented at national and international conferences and published in a peer-reviewed journal. - Trial registration number DRKS00024061, EudraCT: 2020-006001-35.
Online veröffentlicht: 20. September 2023
Gesehen am 20.12.2023